Sistem Informasi Penjualan Dan Pembelian Pada Noya Studio23 Berbasis Desktop - Novia, Triani; Sudrajat, Ari (Jurnal Mahasiswa Terapan; Vol 1 No 2 (2025): Jurnal Mahasiswa Terapan, 2025)
This study aims to develop a desktop-based sales and purchase information system using Microsoft Visual Studio 2010 and MySQL database to address operational issues. The analysis was conducted using the PIECES method, while the system development followed the SDLC model with a waterfall approach. Data were collected through interviews, observations, and documentation. The system design included creating Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), normalization, and interface design. System testing was performed using Black-Box Testing and User Acceptance Testing (UAT). The Black-Box Testing results indicate that the system fulfills all expected functions, while the UAT results show a user satisfaction rate of 96.25%, categorized as very good. These findings demonstrate that the developed system is effective in supporting sales and purchase processes and serves as a practical solution to improve operational efficiency.